Alternative Empowerment Program in narcotics-prone areas and implications for family resilience - Rahmawati, Fika Dewi; Munandar, Adis Imam; Samputra, Palupi Lindiasari (University of Merdeka Malang, 2021)
Community empowerment through alternative activities in narcotic-prone areas is needed to minimize narcotics circulation. This activity aims to analyze the effectiveness of the Alternative Empowerment Program that has been carried out by the Indonesian National Narcotics Agency for North Jakarta City. The method used is qualitative with descriptive analysis. The activity was carried out in RW 12, Muara Bahari Village, Tanjung Priok, North Jakarta. Collecting data through observation and interviews with field implementing officers, community leaders, and residents who take part in alternative empowerment programs. Analysis of the effectiveness of the program was carried out after the alternative empowerment activities were carried out for 2 years. The results of the Alternative Empowerment Program are in accordance with the needs and implementation in the field. The program can increase economic independence and welfare but has not been maximized in reducing the number of narcotics crimes, crimes, and professions for people in vulnerable areas. Through the Alternative Empowerment Program, there will be a strengthening of the household economy which can increase family resilience for people in narcotic-prone areas.